Proliferation Potential of 18-Month-Old Callus of Ananas comosus L. cv. Moris - A.E. De Silva; M.A. Kadir; M.A. Aziz; S. Kadzimin (The Scientific World Journal)
Differential effect of plant growth regulators and additives in proliferation of 18-month-old calli of Ananas comosus L. cv. Moris were assessed in vitro. The proliferation of callus relied on the growth regulators and additives. Of the different auxins supplemented in the Murashige and Skoog (MS) media, 32.22 μM α-naphthaleneacetic acid (NAA) gave the highest mean fresh weight of callus (46.817 g). Medium supplemented with 2,4-dichlorophenoxyacetic acid (2,4-D) was inferior to NAA, while b-naphthoxy acetic acid (BNOA) and p-chlorophenoxy acetic acid (4-CPA) were not effective in proliferating 18-months old callus. Addition of casein hydrolysate and coconut water to NAA supplemented medium showed better proliferation and production of callus. However, in terms of callus production, NAA at 32.22 μM was economically better.